2020
DOI: 10.1177/0898264320923245
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Social Isolation: Comparing the Relationship between Frailty and Unidimensional and Multifactorial Models of Social Isolation

Abstract: Objective: The aim of the study was to compare uni- and multidimensional models of social isolation to improve the specificity of determining associations between social isolation and frailty. Methods: The study included participants aged ≥60 years from the English Longitudinal Study of Ageing assessed for social isolation and frailty (frailty index and Fried phenotype) over a 4-year period. Factor analysis assessed whether social isolation was multidimensional. Multiple regression analysis was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…Social isolation was an in uential factor in the worsening transition between the stages of frailty. These results are similar to those of previous studies [21][22][23]34]. However, previous studies had limitations in that the multidimensionality of social isolation was not considered and the in uence on each step of transition between the stages of frailty could not be analyzed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Social isolation was an in uential factor in the worsening transition between the stages of frailty. These results are similar to those of previous studies [21][22][23]34]. However, previous studies had limitations in that the multidimensionality of social isolation was not considered and the in uence on each step of transition between the stages of frailty could not be analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…The social network of the elderly is mostly composed of family and long-term friends [26], and the number of people with whom important issues could be discussed continues to decrease [27]. Such an increase in social isolation among older adults is thus predicted to be an important risk factor of frailty [21][22][23]. However, only a few studies have investigated the correlation between the multidimensional properties of social isolation (subjective and objective social isolation) and the stages of frailty.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested to consider whether any possible association between the number of NCDs and social isolation could be explained by the presence of frailty after previous work in ELSA that found that social isolation predicted higher frailty levels, and higher frailty levels predicted greater social isolation [ 39 ]. In our study, adjustment for frailty did not remove associations between social isolation and NCDs in women, possibly because there were low numbers of individuals living with frailty in our population sample.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of NCDs in older adults is often accompanied by frailty [ 34 , 35 ], a multi-dimensional geriatric syndrome that can be defined as a state of increased vulnerability resulting from decreased physiological reserves, multi-system dysregulation and limited capacity to maintain homeostasis [ 36 , 37 ]. Frailty is associated with higher risks of falls, disability, hospitalisation and mortality [ 38 ], and it has been reported to predict increased social isolation [ 39 ]. It is thus possible that any link between NCDS and social isolation might be mediated by frailty.…”
Section: Introductionmentioning
confidence: 99%